(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The paper examines an importance of symbolism of microcosm engaged even into the bioterrorism rethoric used in the past September 11 (2001) media language in American public and politics and also on present public narration. The object of our review and study is a more constructive, cultural image of a bug (also ‘electronic bug’), worm or insect as an element of various discourses in American media culture after terrorist 9/11 attacks in 2001. Since those events the approach to microcosm was stimulated in USA by the imagination of fears derived from the parthenogenesis, mass, parasitism, amorphous structures, destructive decays...etc. These figures of meaning are primarily attached to mostly pejorative content. The instrumental use of micrology for military and terrorist purposes today is a matter of common knowledge. Direct bio-attacks in that period of 2001-2002 were indirectly treated as a threat to the freedom of information exchange, and on the other, as a disturbing attempt to anticipate possible counterattack from the side of the U.S. Viruses, germs, bacteria or other pathogens, as semiotic and symbolic prolongation of the threat of "foreigners", especially terrorist forces. The main method of research which is involved within the article is desk research and review of American popular media – both paper and elctronic forms.